What do bones tell us? The study of human skeletons from the perspective of forensic anthropology. (1st December 2015) - Corrieri, Brigida; Márquez-Grant, Nicholas
Human remains are present in a number of contexts. Some of these are archaeological burial sites, which can comprise individual or mass graves burials. Human remains are usually found buried (or cremated), but they can also be found in museums and in universities, as part of their anatomical collections. Human remains can be found in churches as relics, in ossuaries, and as part of objects. Hence human remains refer to not just a complete skeleton, but also a part of a bone or tooth, hair and mummified remains. In more recent forensic, police or medico-legal cases, human skeletal remains can be found in a number of contexts, such as fire scenes, natural disasters, clandestine graves, or on the surface in open areas (e.g. a woodland). One aspect of physical anthropology is that which studies human skeletal remains in order to reconstruct the past, understand human variation, and provide information about the deceased individuals, such as their age at death, sex, ancestry, stature, pathological conditions or traumatic injuries; the remains from medico-legal or police cases fall under the branch of forensic anthropology.